Low acyl gellan gum immobilized Lactobacillus bulgaricus T15 produce d-lactic acid from non-detoxified corn stover hydrolysate - Yongxin Guo; Yuru Zhao; Yuan Gao; Gang Wang; Yixin Zhao; Jiejing Zhang; Yanli Li; Xiqing Wang; Juan Liu; Guang Chen (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Straw biorefinery offers economical and sustainable production of chemicals. The merits of cell immobilization technology have become the key technology to meet d-lactic acid production from non- detoxified corn stover. In this paper, Low acyl gellan gum (LA-GAGR) was employed first time for Lactobacillus bulgaricus T15 immobilization and applied in d-lactic acid (D-LA) production from non-detoxified corn stover hydrolysate. Compared with the conventional calcium alginate (E404), LA-GAGR has a hencky stress of 82.09 kPa and excellent tolerance to 5-hydroxymethylfurfural (5-HMF), ferulic acid (FA), and vanillin. These features make LA-GAGR immobilized T15 work for 50 days via cell-recycle fermentation with D-LA yield of 2.77 ± 0.27 g/L h, while E404 immobilized T15 can only work for 30 days. The production of D-LA from non-detoxified corn stover hydrolysate with LA-GAGR immobilized T15 was also higher than that of free T15 fermentation and E404 immobilized T15 fermentation. In conclusion, LA-GAGR is an excellent cell immobilization material with great potential for industrial application in straw biorefinery industry. Graphical Abstract